PENERAPAN DOKTRIN JURIDISCHE/SYSTEMATISCHE SPECIALITEIT TERHADAP IRISAN ANTARA TINDAK PIDANA PENERIMAAN SUMBANGAN DANA KAMPANYE PEMILU DENGAN TINDAK PIDANA PENCUCIAN UANG - Yanuar, Muh. Afdal (The Prosecutor Law Review, 2025)
In reality, it is not uncommon for lex specialis derogat legi generali principle to be unable to resolve the problem of conflict between special norms and other special norms, inter alia, between the Article 339 paragraph (1) letter c of the Election Law provision and criminal acts provision in AML Law. This article aims to analyze the rationality of juridische/systematische specialiteit doctrine as an appropriate concept in analyzing these problems, as well as determining the provisions that should be applied in the intersection between criminal acts related to election campaign fund donations and money laundering crimes based on the juridische/systematische specialiteit doctrine. This research was using a normative research method with a conceptual and statutory approach. Through this article, it is concluded that juridische/systematische specialiteit doctrine is used as the right concept in analyzing conflicts between special norms and other special norms because this concept more clearly describes legal certainty in determining which special norms must be enforced, and in line with the 'basis for interpreting criminal norms' in interpreting a criminal law norm. Furthermore, based on the juridische/systematische specialiteit doctrine, the provisions in the AML Law, and not the provisions in the Election Law, should be the choice to be implemented in the event of 'laundering of proceeds' in the receipt of campaign funds.